1971
DOI: 10.1111/j.1471-4159.1971.tb00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Brain Serotonin Synthesis by Dibutyryl‐cyclic Amp in Rats

Abstract: Cyclic AMP and dibutyryl‐cyclic AMP, a derivative of cyclic AMP resistant to phosphodiesterase inactivation, were injected into the lateral ventricles of rats. These nucleotides did not change the level of brain 5‐HT but increased the brain level of its principal metabolite, 5‐hydroxyindoleacetic acid. Cyclic AMP was less potent than dibutyryl‐cyclic AMP. Butyrate and 5′‐AMP were inactive. The effect of dibutyryl cyclic AMP on 5‐HT metabolism was studied both in vivo and in vitro. The rate of synthesis of 5‐HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1973
1973
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…Unlike the effect of a single injection, serum total tryptophan increased with significant increases in the con tents of brain tryptophan, 5-HT and 5-HIAA. These findings are in essential agreement with previous reports (8,15). Results are given as means ± S.E.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Unlike the effect of a single injection, serum total tryptophan increased with significant increases in the con tents of brain tryptophan, 5-HT and 5-HIAA. These findings are in essential agreement with previous reports (8,15). Results are given as means ± S.E.…”
Section: Resultssupporting
confidence: 94%
“…However, it did not cause detectable changes in the brain contents of tryptophan, 5-HT and 5-HIAA. On the other hand, in agree ment with previous reports (8,15), our results showed that subacute treatment with lithi um increased the brain contents of tryptophan, 5-HT and 5-HIAA and serum total trypto phan. Fractionation of the serum total tryptophan showed, however, that free tryptophan decreased and tryptophan bound to serum protein increased.…”
Section: Discussionsupporting
confidence: 94%
“…For example, pyrrolase can compete for tryptophan (Curzon & Green, 1971) and other amino acids can interfere with its uptake by the brain (Fernstrom & Wurtman, 1972b;Oldendorf, 1971). Finally, it is possible that drugs which influence cyclic AMP metabolism may affect brain tryptophan not only by altering lipolysis but also through cyclic AMP changes in brain membranes as Tagliamonte, Tagliamonte, Forn, Perez-Cruet, Krishna & Gessa (1971) report that cyclic AMP (albeit in pharmacological dosage) increases tryptophan uptake by brain slices in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…This exhibits diurnal variations and may be affected by the activity of central catecholaminergic systems (Hery, Rouer, Kan & Glowinski, 1974) and cyclic adenosine-3 ',5 '-monophosphate (cyclic AMP) (Tagliamonte, Tagliamonte, Forn, Perez-Cruet, Krishna & Gessa, 1971).…”
Section: Introductionmentioning
confidence: 99%